Modelo de gestión financiera integral para MIPYMES en Colombia (2009)
ABSTARCT: MSMEs represent as a whole most of the companies in the country. In this sense, and given the exigencies and continuous changes in the business environment, these organizations must move towards incorporating a comprehensive financial management model that allows the harmonization of all their areas in order to achieve their mission objectives. For that reason, the accounting information system, finances, and strategic planning play a key role in the interest of correct decision making and a good corporate management.